2019
DOI: 10.1002/ejic.201900060
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine‐Free Facile Synthesis of Palladium‐Tetrakis(Triphenylphosphine)

Abstract: We present an easy and very efficient procedure for the synthesis of Pd(PPh 3 ) 4 using nontoxic reducing agents. The complex is obtained in a remarkable 83 % yield, and the [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Having established that the catalytic process occurs primarily by reaction of hydrazine with arylpalladium chloride complexes (such as 4), we sought to determine the ratelimiting step.The initial rates imply that the rate-limiting step could be deprotonation of hydrazine to give an arylpalladium-(II) hydrazido species or reductive elimination of aryl hydrazine after reversible generation of the arylpalladium hydrazido species.I fd eprotonation of hydrazine is rate limiting, then aprimary KIE would be observed for reactions with hydrazine and hydrazine-d 4 .I fr eductive elimination of aryl hydrazine is rate-limiting,t hen as econdary or equilibrium KIE would be observed. Initial rates of the reaction of hydrazine-d 4 and potassium deuteroxide as base with 1b as chloroarene versus those with protiated hydrazine monohydrate,a nd potassium hydroxide revealed ap rimary KIE of 3.7 (7). This value is consistent with rate-limiting deprotonation of hydrazine (Scheme 7).…”
Section: Angewandte Chemiesupporting
confidence: 62%
See 1 more Smart Citation
“…Having established that the catalytic process occurs primarily by reaction of hydrazine with arylpalladium chloride complexes (such as 4), we sought to determine the ratelimiting step.The initial rates imply that the rate-limiting step could be deprotonation of hydrazine to give an arylpalladium-(II) hydrazido species or reductive elimination of aryl hydrazine after reversible generation of the arylpalladium hydrazido species.I fd eprotonation of hydrazine is rate limiting, then aprimary KIE would be observed for reactions with hydrazine and hydrazine-d 4 .I fr eductive elimination of aryl hydrazine is rate-limiting,t hen as econdary or equilibrium KIE would be observed. Initial rates of the reaction of hydrazine-d 4 and potassium deuteroxide as base with 1b as chloroarene versus those with protiated hydrazine monohydrate,a nd potassium hydroxide revealed ap rimary KIE of 3.7 (7). This value is consistent with rate-limiting deprotonation of hydrazine (Scheme 7).…”
Section: Angewandte Chemiesupporting
confidence: 62%
“…[6] Pd-catalyzed couplings of hydrazine are difficult to develop because hydrazine is as trong reductant and can reduce Pd II species to catalytically inactive Pd black. [7] Moreover,h ydrazine contains multiple N À Hb onds and can undergo multiple couplings.A lthough prior reports by Stradiotto [6a,b] and Buchwald [6c] showed that the hydrazine can couple with aryl halides,t hese reactions have required NaOtBu as base and high loadings of catalyst (1-20 mol %). This base and these loadings make this reaction impractical for production of simple aryl hydrazines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a relatively acute L-M-L angle of 90°no tetra substitution was observed even after addition of a large excess of PPh 3 , unlike in the case of Pd 0 where steric congestion is reduced in a tetrahedral coordination environment. 94,95…”
Section: Metal-ligand Bindingmentioning
confidence: 99%
“…A rough estimate of the ratio between the three formyl peaks yields 2:2:1 for TIAM:5:3, showing that the main competitor for TIAM is 5. The succeeding reactions using Pd(PPh 3 ) 4 were then monitored based on the ratios of the distinct formyl peaks and would be stopped only for two reasons: when the TIAM peak became higher than that of 5 or when the aryl peaks that were identified to belong to the phosphine ligand were no longer increasing [54].…”
Section: Results Of Suzuki Couplingmentioning
confidence: 99%
“…The technique allowed the separation and identification of a mono-subsituted side-product, 6 (fraction 2, IMAF-062-F2), which eluted in DCM; and from what was initially identified to be TIAM (colorless fraction 4, IMAF-062-F4) which eluted in 3% EtOH in DCM (Fig.3.8). The remaining yellow band on the column (IMAF-064-F5) was also collected in 10% EtOH in DCM, with the 1 H NMR spectrum showing the aromatic peaks of the phosphine ligand[54].…”
mentioning
confidence: 99%